Three-dimensional secondary reconstruction of mistreated zygomatic fractures using patient specific surgical guides and implants - Krasovsky, Andrei; Hija, Ahmad; Zeineh, Nidal; Bilder, Amir; Emodi, Omri; Rachmiel, Adi; Shilo, Dekel (Frontiers in Oral Health, 2024)
IntroductionThe zygomatic bone has a great impact on the anterior and lateral projection of the midface as well as the proper position of the globe. Primary alignment of zygomatic fractures is very important as secondary reconstruction is far more challenging. Treatment of misaligned zygoma requires refracturing of the bone to allow for repositioning. Due to the great impact of the zygoma on the projection of the midface, a precise 3D realignment is of great importance. Technology nowadays develops rapidly and allows for superior results in many surgical fields. The use of patient specific surgical guides and fixation plates is becoming more abundant.MethodsUsing 3D segmentation and design software, we developed a sequence for using 3D planning and printing both for the refracturing stage, avoiding a coronal approach, and for precise repositioning and fixation of the zygoma in the new position.ResultsThe method is described as well as a unique advanced 3D analysis, allowing for objectively assessing the results. Two cases are presented, including the design and post operative changes.DiscussionPre-op, planned and final positions were compared and showed exceptional accuracy allowing for the elimination of human errors which are common in a 3D sensitive procedure such as refracturing of the zygoma. This method can easily be applied to other secondary reconstruction procedures requiring realignment.